Analisis Kinerja Keuangan dengan Menggunakan Metode Value For Money dalam Mengukur Kinerja Pelayanan Sektor Publik: Studi Kasus di Dinas Kesehatan Kabupaten Cianjur - Gatot Wahyu Nugroho; Andri Indrawan; Mukhamad Muslim Habibie (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was conducted at the Cianjur Regency Health Office. The purpose of this study was to evaluate the financial performance of the Cianjur Regency Health Office in 2022 to 2023 using the Value for Money method. This research uses descriptive qualitative research. The data used in this study consisted of Primary Data and Secondary Data. Primary data was obtained through interviews with the Head of the Finance Department related to the Accountability Statement Report (LKPJ). Meanwhile, Secondary Data was collected from literature relevant to this research. The results showed that the financial performance of the Cianjur Regency Health Office on the Economic Ratio in 2022-2023 was good. However, performance on the Efficiency Ratio and Effectiveness Ratio cannot be categorized as efficient and effective from several programs implemented.